The Relationship Between Self-Efficacy and Perceptions of Different Literacy Types Among College Students. Issue 1 (2nd January 2017) - Bui, Ngoc H.
Abstract : Studies on reading literacy have yet to connect how students perceive the importance of different literacy areas to their ability perception in those areas. This article analyzes students' importance ranking of four different areas of literacy: prose (comprehending written information), document (interpreting information in forms, schedules, tables, and graphs), quantitative (using and comprehending numbers found in written material), and health (using health-related information). It was expected that perceptions of literacy importance would be related to self-efficacy and that students would rank quantitative literacy as the lowest in importance. As hypothesized, self-efficacy and importance rankings were positively related among 250 undergraduates (67 males, 183 females; Mean age = 21.88) who completed online surveys. Also, the importance ranking of and perceived ability in quantitative literacy were lower than the other literacy types. Although quantitative literacy is a significant indicator for future career success, participants do not perceive this area as valuable, nor do they have confidence in their quantitative literacy abilities. Limitations, implications, and suggestions for future research are discussed.